2014
DOI: 10.1111/anu.12082
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative dietary leucine requirement of juvenile Pacific white shrimp,Litopenaeus vannamei(Boone) reared in low-salinity water

Abstract: The experiment was conducted to determine the leucine requirement of juvenile Pacific white shrimp Litopenaeus vannamei (Boone) in low-salinity water (0.50-1.20 g L À1 ). Six diets were formulated to contain 410 g kg À1 crude protein with fish meal, peanut meal and precoated crystalline amino acids with different concentration of L-leucine (16.72, 19.60, 22.06, 24.79, 27.28 and 30.16 g kg À1 dry diet). Each diet was randomly assigned to triplicate groups of 30 shrimps (0.38 AE 0.002 g), and the feed trial las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 41 publications
2
27
1
Order By: Relevance
“…Leucine deficiency or excess may result in a reduction in the growth performance of Senegalese sole, Solea senegalensis (Aragão et al, 2004). In juvenile pacific white shrimp (Litopenaeus vannamei), increasing dietary leucine beyond 2.50% reduced the growth performance and feed utilization (Liu et al, 2014). The feed F I G U R E 1 Relative gene expressions of TOR (a), 4E-BP2 (b), S6K1 (c), eIF4E (d) and LARS (e) in the hepatopancreas and muscle of gibel carp fed diets with different leucine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Leucine deficiency or excess may result in a reduction in the growth performance of Senegalese sole, Solea senegalensis (Aragão et al, 2004). In juvenile pacific white shrimp (Litopenaeus vannamei), increasing dietary leucine beyond 2.50% reduced the growth performance and feed utilization (Liu et al, 2014). The feed F I G U R E 1 Relative gene expressions of TOR (a), 4E-BP2 (b), S6K1 (c), eIF4E (d) and LARS (e) in the hepatopancreas and muscle of gibel carp fed diets with different leucine levels.…”
Section: Discussionmentioning
confidence: 99%
“…The diet‐related mortality was observed in the dietary valine with 15.0 g/kg, which had not been found in tiger shrimp (Millamena & Teruel, ). The excess amount of dietary leucine could decrease survival rate of golden pompano and Pacific white shrimp (Huang et al., ; Liu et al., ). Valine deficiency causes lower immune ability and the serious damage of liver, eventually leading to the death of fish (Chen et al., ; Deng et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The excess amount of dietary leucine could decrease survival rate of golden pompano and Pacific white shrimp (Huang et al, 2015;Liu et al, 2014). Valine deficiency causes lower immune ability and the serious damage of liver, eventually leading to the death of fish (Chen et al, 2012;Deng et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The similar procedure was used to determine the dietary leucine requirement of juvenile L. vannamei at 0.50–1.20 psu (Liu et al . ) and the L‐isoleucine (precoated crystalline) requirement at 0.50–0.70 psu (Liu et al . ).…”
Section: Nutritional Requirements Of Litopenaeus Vannamei At Low Salimentioning
confidence: 99%
“…37.8 g protein kg À1 on dry matter). The similar procedure was used to determine the dietary leucine requirement of juvenile L. vannamei at 0.50-1.20 psu (Liu et al 2014a) and the L-isoleucine (precoated crystalline) requirement at 0.50-0.70 psu (Liu et al 2014b). The results showed that low or excess amount of dietary leucine could decrease growth performance of L. vannamei.…”
Section: Nutritional Requirements Of Litopenaeus Vannamei At Low Salimentioning
confidence: 99%